EFEK PERPINDAHAN TELEVISI DAN ORIENTASI FUNGSIONAL ANAK PADA MEDIA - Dewi, Yuni Retna (Universitas Prof. Dr. Moestopo (Beragama), 2006)
The title of this paper is âDisplacement Effect of TV and The childâs functional Orientation to Mediaâ.This paper is to discuss the issue in â Wacanaâ as a scientific Journal published by FIKOM UPDM (B), which is meant to broaden perspective in conducting research in mass communication.For that purpose, the writer had made some analysis on the research conduct by IR Brown, JK Grammond, and RJ Wide entitled â Displacement Effect of Television and the âChildâs Functional Orientation to the Mediaâ, which is related to the use of Mass Communication Current Perspective on Gratification Research published by Jay. G. Blummer and Elenn Katz.The research published by JR. Brown and his colleagues is focused on the displacementâs effects of TV and other mass communication media, such as books, comics, radio, and newspaper.This study tries to find out how effective the media is in influencing the development of childâs who has sufficient facilities and who has not, where situsional and social factors are included to be necessarily considered in this study, such as where the children live, how the children spent their time, and what the media meant to them.